Investigational ABC transporter inhibitors - Falasca, Marco; Linton, K. (2012)
Introduction: Multidrug resistance (MDR) is the main cause of failure in cancer therapy. One mechanism responsible for MDR is the active efflux of drugs by ATP-binding cassette (ABC) transporters. Several agents have been developed to block transporter-mediated drug efflux and some of these compounds have entered Phase II/III clinical testing. Evidence is also emerging of the role played by ABC transporters in cancer cell signalling that is likely to be important in disease progression and which is distinct from MDR. Areas covered: This article reviews current literature to analyse the rationale for targeting ABC transporters in cancer. Preclinical and clinical results of ABC transporter inhibitors in early clinical trials, as single agents or in combination with other drugs, are described. The development of new strategies to target MDR and the emerging roles of ABC transporters in cancer signalling are discussed. Expert opinion: The intense active search for safe and effective inhibitors of ABC transporters has led to some success in MDR reversal in preclinical studies. However, there has been little impact on clinical outcome. The discovery of novel, potent and nontoxic inhibitors as well as new treatment strategies is therefore needed. © 2012 Informa UK, Ltd.